PENGARUH KECERDASAN BUATAN UNTUK AUDIT KEUANGAN: MENINGKATKAN EFISIENSI DAN MENGHADAPI TANTANGAN DI ERA DIGITAL - Munawarah, Israfil (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
Abstract:The digital age brings a surge of complex financial data, challenging traditional auditing methods. Artificial Intelligence (AI) comes as a solution, offering increased efficiency and effectiveness of financial audits. This research explores the challenges and opportunities that arise from the integration of AI in the financial audit process. Key issues discussed include the adaptation of traditional audit methodologies to AI, the reliability of AI-guided analysis, and the ethical implications of automation in decision making as well as how AI is revolutionizing the audit process, from automation of routine tasks, identification of patterns and anomalies, to predictive analysis for risk assessment, AI has great potential to improve financial auditing in the digital age. With responsible and ethical application, AI can assist auditors in providing better assurance and increasing public confidence in financial integrity. The research aims to understand how AI affects audit efficiency and accuracy. Using a mixed methods approach, combining quantitative data analysis and qualitative case studies, the research investigated auditors' and organizations' experiences in implementing AI tools. Findings highlight the changing role of auditors in utilizing AI, emphasizing the need for continuous professional development. This research provides valuable insights in the ongoing discourse on the transformative effects of AI in financial auditing. Keywords: Artificial Intelligence (AI); Financial Audit; Audit Methodology; Efficiency and Accuracy; Professional Development.